MEASURING THE IMPACT OF JIGSAW TECHNIIQUE FOR COMMUNITY LANGUAGE LEARNING IN DIPLOMA OF MEDICAL EDUCATION: A FUTURE CHALLENGE ENGLISH STUDY - Ardiansyah, Lalu Dwi Satria; Permana, Yan Reiza (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Modern medical education demands a shift from passive to active learning to build professional competence, yet EFL students in Indonesia often face significant barriers to speaking skills, such as limited vocabulary and low self-confidence. This quasi-experimental study aimed to evaluate the impact of implementing the Jigsaw technique in Community Language Learning (CLL) on the speaking skills of Diploma students, focusing on vocabulary, accuracy, fluency, and pronunciation. The study involved 48 Bima International University students who were randomly divided into a control group (N=20) and a Jigsaw experimental group (N=28). The study used a mixed-methods design integrating quantitative testing and classroom observations. The data analysis revealed a statistically significant difference favoring the Jigsaw group, with students in this group demonstrating significantly better speaking performance than the control group across all tested competencies. These findings confirm that the Jigsaw CLL technique is effective in improving oral proficiency, transforming students into active learners, and reducing communication anxiety. Therefore, this method is recommended as an essential pedagogical strategy for improving the quality of English language learning in medical education contexts. ABSTRAK Pendidikan medis modern menuntut pergeseran dari pembelajaran pasif ke aktif untuk membangun kompetensi profesional, namun mahasiswa EFL di Indonesia sering menghadapi kendala signifikan dalam keterampilan berbicara, seperti keterbatasan kosa kata dan rendahnya kepercayaan diri. Penelitian kuasi-eksperimental ini bertujuan untuk mengevaluasi dampak penerapan teknik Jigsaw dalam Community Language Learning (CLL) terhadap kemampuan berbicara mahasiswa Diploma, dengan fokus pada aspek kosa kata, akurasi, kelancaran, dan pengucapan. Studi ini melibatkan 48 mahasiswa Universitas Bima Internasional yang dibagi secara acak menjadi kelompok kontrol (N=20) dan kelompok eksperimen Jigsaw (N=28), menggunakan desain metode campuran yang mengintegrasikan tes kuantitatif dan observasi kelas. Hasil analisis data menunjukkan perbedaan statistik yang signifikan yang mengunggulkan kelompok Jigsaw, di mana mahasiswa dalam kelompok ini menunjukkan kinerja berbicara yang jauh lebih baik dibandingkan kelompok kontrol pada seluruh kompetensi yang diuji. Temuan ini mengonfirmasi bahwa teknik Jigsaw CLL efektif dalam meningkatkan kemahiran lisan, mengubah mahasiswa menjadi pembelajar aktif, serta mengurangi kecemasan dalam berkomunikasi. Oleh karena itu, metode ini direkomendasikan sebagai strategi pedagogis esensial untuk meningkatkan kualitas pembelajaran bahasa Inggris dalam konteks pendidikan medis.